Life buoy - Md Shahudin, Shamil Najmy; Zainal, Abdul Rahem; Othman, Siti Amira (Penerbit UTHM, 2020)
A lifebuoy such as figure 1, or we can call as ring buoy, lifering, lifesaver, life donut, life preserver or lifebelt, also known as a "perry buoy", or "kisby ring". The "kisby ring", or sometimes will be call "Kisbie ring", is thought to be named after Thomas Kisbee (1792–1877) who was a British naval officer. Lifebuoy is a lifesaving buoy designed to save someone in the water. It also can provide buoyancy and prevent drowning. To improve aid rescue at night, mostly lifebuoys are fitted with one or more seawater-activated lights.